b + c = 5/4 + ( -7/12) = 15 /12 - 7 /12 =(15 - 7) /12
= 8/12 = ( 2 x4) / (3x4) = 2 / 3
A = - 1 /3 x ( 2/3) = ( - 1x2 ) /( 3 x 3 )= - 2/ 9
1/b = 4/5 a/c = a x 1/c = -1/3 x ( -12 /7) = + ( 1 x12) /( 3 x7) = 4/7
B = 4 /5 + 4/7 = 4 x ( 1 /5 + 1/7 )= 4 x ( 7 + 5) /(5 x7) = (4x 12) /( 5x7)
B = 48 / 35
1/2 c = 1/2 x ( - 7/12) = ( -1x7 ) /( 2x 12) = - 7 /24
-3b = ( - 3 x 5) / 4 = - 15/4 = -(15x6 ) /( 4x6) = - 90 / 24
2c = 2 x( -7/12 ) = - 14 /12 = - 28 / 24
C = - 7/24 - 90/24 - 28/24 = ( -7 - 90 -28) / 24 = -125 /24